STRUKTUR MANTRA KAGANCANGAN DALAM NASKAH MANTRA MISTIK - Dede Hidayatullah (Balai Bahasa Kalimatan Selatan, 2018)
The kagancangan mantra is a mantra that produces supernatural power both on the hand or body to hit. This kagancangan mantra is useful for creating strength on the body generally and on the hand specifically. This research will describe the kagancangan mantra, the structure and language used. The data of this study are six mantras found in the 'Mystical Mantra' (MM), the text written in code E. 4508. The result shows that each mantra of these six kagancangan mantra has its own rituals, methods and prohibitions. The structure of the kagancangan mantra consists of elements such as the title, opening, and suggestion elements, and there are also mantra that consists of element of the title and element of suggestion only. Meanwhile the purpose is implied by the element of purpose and the element of suggestion. The language of the kagancangan mantra consists of Banjar language; combination of Banjar and other languages, especially Arabic; and only Arabic.Key words: mantra, kagancangan, structure, and language